2009
DOI: 10.1074/jbc.m805894200
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10, the Rate-limiting Protease of Regulated Intramembrane Proteolysis of Notch and Other Proteins, Is Processed by ADAMS-9, ADAMS-15, and the γ-Secretase

Abstract: ADAM10 is involved in the proteolytic processing and shedding of proteins such as the amyloid precursor protein (APP), cadherins, and the Notch receptors, thereby initiating the regulated intramembrane proteolysis (RIP) of these proteins. Here, we demonstrate that the sheddase ADAM10 is also subject to RIP. We identify ADAM9 and -15 as the proteases responsible for releasing the ADAM10 ectodomain, and Presenilin/␥-Secretase as the protease responsible for the release of the ADAM10 intracellular domain (ICD). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
152
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(166 citation statements)
references
References 72 publications
(108 reference statements)
8
152
1
1
Order By: Relevance
“…1E). Nondenaturing solubilization of the membrane pellet (or the hippocampus as a whole) in 1% CHAPS buffer greatly increased the extraction of a truncated, transmembrane C-terminal ADAM10 fragment (A10CTF) (13). Using a subcellular prefractionation protocol, we found that membrane expression of precursor A10 (pA10) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1E). Nondenaturing solubilization of the membrane pellet (or the hippocampus as a whole) in 1% CHAPS buffer greatly increased the extraction of a truncated, transmembrane C-terminal ADAM10 fragment (A10CTF) (13). Using a subcellular prefractionation protocol, we found that membrane expression of precursor A10 (pA10) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we repeated the Nrp1 staining analyses with rat proprioceptive and cutaneous axons that were cultured in the presence of the broad-spectrum MP inhibitor, TAPI-1 [46][47][48][49] (Fig. 2 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[54][55][56] It has been suggested that the ADAM9 is not able to directly cleave APP protein at a-secretase site, but that its a-secretase activity could be related to ADAM9 regulation of ADAM10 activity. 17,57 We have detected all three ADAMs in mouse brain microvessels and human BMECs. Interestingly, endothelial deletion of PPARd in mouse decreased sAPPa production, accompanied by a significant reduction of ADAM10 expression and increased ADAM17 protein level, indicating that in brain microvessels sAPPa production is primarily determined by activity of ADAM10.…”
mentioning
confidence: 99%